Influence of circumferential gap on the axial compressive behaviour of circular CFDST stub columns: Tests, numerical analysis and design method - Pei-Jia Dai; Rui Wang; Hui Zhao; Wen-Da Wang; Man-Tai Chen (Engineering Structures, 2026)

Photodegradation remodels plastic carbon pool: Unveiling transformation and fate of particulate, dissolved and gaseous carbon fractions - Taishuo Zhang; Rui Wang; Jian Wang; Zhengyang Shang; Jiarui Zhao; Xiaoqian Ye; Zixuan Zhang; Xinrui Zhang; Haiyu Zhang; Ziyan Li; Peng Liu; Hanzhong Jia (Water Research, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Microbiome dysbiosis and metabolic reprogramming in kiwifruit peel during Botrytis cinerea infection - Jingsheng Chen; Rui Ma; Yu Zhao; Yuan Sui; Zhuo Chen; Xianmei Xiao; Zhenshuo Wang; Jia Liu (Postharvest Biology and Technology, 2026)

Endogenous impurity regulation in solid waste-derived hydroxyapatite: From single-phase defects to in-situ multiphase reconstruction - Qingning Bai; Tongyu Liu; Xiaoyan Zhao; Zhiyu Chen; Shuo Cui; Jiayu Feng; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia; Fang Wang (Journal of Environmental Chemical Engineering, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Cyclic dynamic behavior of rockfill material in three-dimensional stress state - Jia Zhao; XueFeng Li; Rui Wang (Computers and Geotechnics, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Description of two novel Marinobacter species isolated from saline-alkali soil: Marinobacter alkalisoli sp. nov. and Marinobacter shunpengi sp. nov - Jing-Yan Zhao; Lian Xu; Rui-Qi Sun; Mei-Qian Song; Jia-Hui Zeng; Hua-Mei Wei; Ji-Quan Sun (Systematic and Applied Microbiology, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Dietary ellagic acid improves glucose and lipid homeostasis with concurrent gut microbiota and serum metabolome remodeling in db/db mice - Rui-Bo Jia; Weipei Li; Pengru Yan; Chunxia Zhou; Zirui Huang; Mouming Zhao (Food Bioscience, 2026)

Subchronic PM2.5 exposure exacerbates chronic stress-induced depression-like pathology in mice - Haoyu Lu; Xiaohui Zhao; Ran Ning; JunKoo Yi; Zhongmei He; Yan Zhao; Jianan Geng; Jia Zhou; Weijia Chen; Rui Du (Environmental Research, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

Modification of Ce−Fe oxide by quenching induced trace Sn doping for accelerating chlorobenzene oxidation - Juexiu Li; Wenbo Xue; Huandan Cui; Yige Xi; Rui Zhao; Yin Liu; Zhongxian Song; Kajia Wei; Ziqiang Li; Chuanyi Fan; Kan Li; Jinping Jia (Chemical Engineering Journal, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Corrigendum to “Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process” [Process Safety and Environmental Protection 203 (2025) 107862] - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

The synergistic effect and underlying mechanism of bimetal and its support in cobalt‑lanthanum doped palygorskite-based catalyst for norfloxacin removal through activating persulfate - Ye Li; Jia-Hang Liu; Bai-Hang Zhao; Xu-Ming Liu; Rui-Xuan Liu (Journal of Water Process Engineering, 2026)

Response of anaerobic ammonium oxidation granular sludge to acute GenX exposure: Performance, microbial responses, and mechanistic insights - Xu-Ming Liu; An-Dong Zhao; Bai-Hang Zhao; Lei-Yue Wu; Rui-Xuan Liu; Peng-Biao Jia (Chemical Engineering Journal, 2026)

Cross-instrument coal quality spectral analysis via a PDS-assisted fine-tuning calibration transfer method - Junlong Gao; Jiaxuan Li; Jiaxin Yin; Rui Gao; Zhihui Tian; Yang Zhao; Yu Bai; Lei Dong; Weiguang Ma; Lei Zhang; Wangbao Yin; Suoteng Jia (Analytica Chimica Acta, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Machine-learning-guided risk stratification of bacterial contamination in food powered by a dual-mode lateral flow biosensor using low-crystallinity nanozyme labels - Rui Shu; Sijie Liu; Huilin Jia; Lei zhao; Ibrahim A. Darwish; Jianlong Wang; Daohong Zhang (Food Research International, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Biomass-derived modifiers customize polymeric nanofiltration membranes for enhanced lithium/magnesium ion selectivity - Xin-Xi Ding; Cheng Jiang; Jia-Wang Wang; Zi-Hui Wu; Rui Luo; Yue Zhao; Yue Wang; Dan-Dan Shao (Desalination, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Characterizing on-road particle number emissions from container diesel trucks using interpretable machine learning - Rui-min Hao; Hong-di He; Hong-mei Zhao; Wen-jian Jia; Zhong-ren Peng; Hui Wang (Atmospheric Pollution Research, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Advancement and field evaluation of a honeysuckle harvesting robot with integrated clamping and air-suction mechanisms - Zhaoyu Rui; Zhao Zhang; Cunming Hao; Yingxin Jia; Zhenhuan Ye; Saddam Hussain; Mahmoud A. Abdelhamid; C. Igathinathane; Yiannis Ampatzidis (Computers and Electronics in Agriculture, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

CRISPR/Cas9-mediated knockout of the 22 kDa α-prolamin genes orchestrates the regulation of functional amino acid content in foxtail millet - Rui Zhao; Jiayi Chen; Yongchao Li; Maosheng Jin; Kejin Liu; Yang Liu; Lulu Gao; Guanghui Yang; Xiangyang Yuan; Xiaoqian Chu; Jia-Gang Wang (Journal of Plant Physiology, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Probabilistic modeling of microwave thermal damage at rough rock-cement interfaces using a Bayesian-ANN framework - Jia-Le Li; Fuxin Rui; Yanlong Zheng; Gao-Feng Zhao; Kostas Senetakis (Computers and Geotechnics, 2026)

CRISPR/Cas9-mediated α-prolamin gene (Seita.8G190200) mutagenesis increases the content of functional amino acids in foxtail millet (Setaria italica) - Rui Zhao; Jiayi Chen; Yongchao Li; Dan-Ying Chen; Xueting Kang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Cell Reports, 2026)

Research on rock mechanics parameter prediction based on the frequency spectrum characteristics of vibration while drilling - Jia-kang Song; Jian-ning Wang; Zhao Ma; Yi-guo Xue; Rui-rui Cai; Fan-meng Kong; Lei Gao (Applied Geophysics, 2026)

Heating jacket-like Janus CS/PPy aerogel with gradient-oxidation for high-efficiency solar desalination - Chen Yang; Fuxin Zhao; Rui Jia; Wilberforce Agbley; Yali Liu; Huan Ma; Xuechun Wang; Jianyu Xing (Chemical Engineering Journal, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Polystyrene and its dissolved organic matter accelerate antibiotic resistance gene dissemination in anaerobic digestion by posing resistance pressure on functional microorganisms - Zixuan Zhang; Rui Wang; Zhibo An; Yiming Liu; Jiarui Zhao; Taishuo Zhang; Xiaoqian Ye; Peng Liu; Hanzhong Jia (Water Research, 2026)

Estrogen inhibits granulosa cell apoptosis via nuclear receptors by suppressing death receptor and mitochondrial pathways in goat small antral follicles - Sihai Lu; Baijuan Yue; Yaju Tang; Haoyu Xu; Rui Xu; Xiaoe Zhao; Qiang Wei; Jia Xue; Meng-Hao Pan; Sha Peng; Baohua Ma (Theriogenology, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Biaxially oriented polyethylene film packing and hydrogen sulfide fumigation maintain postharvest quality of tomato fruits by reducing malondialdehyde levels and water loss - Le-Ying Yan; Pedro Garcia-Caparros; Jia-Xin Wang; Wan-Ken Chen; Xiong-Jie Wu; Dong-Bo Zhu; Rui Zhang; Zhao-Zhong Wang; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Nitrogen sites induce homogeneous dispersion of iron species on biochar for enhanced hydrogen sulfide removal in a low-temperature anaerobic environment - Jiayu Feng; Fei Zhao; Huang Xiang; Fang Wang; Shuo Cui; Zibin Pan; Rui Cao; Ping Ning; Lijuan Jia (Bioresource Technology, 2026)

Deciphering indoor summer microbial composition and its health impacts: a study based on university campus in Beijing - Li Guo; Hua Zhao; Rui Du; Zeyu Jia; Yuanyuan Li (Building and Environment, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Phaeovulum Molybdatiresistens sp. nov., a Molybdate-resistant Bacterium Isolated from Eutrophic Pond Water - Jianjun Song; Yuanshuo Qiu; Ke Ma; Yuelin Liu; Jia Wang; Yaqi Liu; Xiaolong Song; Kaiyue Wang; Jinhua Hu; Weidong Mu; Yanfang Zhao; Aijv Liu; et al. (Current Microbiology, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

MXene triggers room-temperature 4D printing of advanced ionic hydrogels for sensitive electronic skin - Qinglong He; Chendong Zhao; Yuanjie Jiang; Jimei Liu; Xinyu Liu; Rui Jia; Cheng Yang; Mengzhou Liao; Yan Zhao; Desheng Kong; Valeria Nicolosi; Caofeng Pan; et al. (Chemical Engineering Journal, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Multiscale structural design integrating mechano-flame retardancy-superhydrophobicity into multifunctional phenolic aerogel - Zhiyan Lu; Zhipeng Liu; Zhe Hu; Li Zhao; Zhen Jia; Zebao Rui (Chemical Engineering Journal, 2025)

Extreme Phenotypic Variation Confounds Acanthocephalan Systematics: A Case Study of Longicollum pagrosomi and Pomphorhynchus zhoushanensis (Acanthocephala: Echinorhynchida) - Cui‐Hong Zhao; Hui‐Xia Chen; Matthew Thomas Wayland; Rui‐Jia Yang; Xiao‐Hong Gu; Liang Li (Zoologica Scripta, 2025)
The phylum Acanthocephala is a ubiquitous group of zooparasites, with major socio‐economic importance. The true diversity of the Acanthocephala is obscured by the phenomena of cryptic speciation and a large degree of intraspecific variation. In this study we describe an example of extreme phenotypic variation in neck morphology. The pomphorhynchid acanthocephalans, Longicollum pagrosomi and Pomphorhynchus zhoushanensis were originally differentiated on the basis of differences in neck morphology; P. zhoushanensis possesses a neck bulb whereas this structure is absent in L. pagrosomi . However, ASAP and phylogenetic analyses of the ITS, 12S, cox 1 and cox 2 sequence data, together with comparative mitogenomics, revealed that the two taxa are in fact conspecific. Therefore, the presence or absence of a neck bulb represents extreme phenotypic variation, and this character is not reliable for distinguishing the genera Pomphorhynchus and Longicollum. In the absence of other characters to discriminate the two genera, Longicollum is relegated to a junior synonym of Pomphorhynchus . A new combination Pomphorhynchus pagrosomi (Yamaguti, 1935) comb. nov. is proposed for L. pagrosomi Yamaguti, 1935 and P. zhoushanensis Li, Chen, Amin & Yang, 2017 is relegated to a junior synonym of P. pagrosomi .

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Seasonal variation of microbial activity in atmospheric particulate matter and its lagging response to environmental factors - Hua Zhao; Rui Du; Li Guo; Yuanyuan Li; Hanlin Chen; Zeyu Jia (Atmospheric Environment, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

New insights into natural organic matter transformation on enhanced membrane performance through peroxymonosulfate activation by Fe-based amorphous alloys - Rui Chen; Qianru Zhao; Bohan Jia; Zhenyong Wang; Yucang Du; Jinsuo Lu (Chemical Engineering Journal, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Nested MPI-CWRF dynamical downscaling and future projections of summer extreme precipitation changes in China - Huan Li; Fengxue Qiao; Nan Wei; Haoran Xu; Rui Wang; Fulin Jiang; Guimin Lou; Jia Zhao; Qingyu Yang (Frontiers of Earth Science, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Source analysis of soil selenium and evaluation of soil environmental quality and safety in the eastern area of Zichuan District, Shandong Province - Jia-Wen Cui; Li-Yuan Yang; Jie-Rui Dai; Xi-Qiang Zhao; Jia-Liang Li (Environmental Monitoring and Assessment, 2025)

Substrate type-driven differences in interfacial microbial community and pathogenic risk: Clay, microplastics and activated carbon - Taishuo Zhang; Wenfu Wang; Xiang Zhi; Xiaoqian Ye; Rui Wang; Jiarui Zhao; Jiamin Dai; Hong Qiang; Peng Liu; Hanzhong Jia (Gondwana Research, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

Arsenolipid-induced reproductive toxicity in Caenorhabditis elegans: Elucidating the mechanism through the HUS-1-CEP-1-EGL-1-CED-9-CED-4-CED-3 signaling pathway - Caiyan Li; Zhuo Wang; Bingbing Song; Kit-Leong Cheung; Jianping Chen; Rui Li; Xiaofei Liu; Xuejing Jia; Qiaoli Zhao; Saiyi Zhong (Food and Chemical Toxicology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

Research on seismic performance and improvement of Chinese rural self-built houses - Jianxiong Zhang; Dewen Liu; Rui Sun; Yong Ding; Yunlong Zhao; Jia Wang; Weiwei Sun (Bulletin of Earthquake Engineering, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Low-damage performance of rocking column bases with Belleville Springs for enhanced seismic resilience - Jiang-Yue Xie; Zhenduo Yan; Junrong Liu; Rui Zhang; Ping Xiang; Xianzhong Zhao; Gregory A. MacRae; G. Charles Clifton; Rajesh P. Dhakal; Shahab Ramhormozian; Geoffrey Rodgers; Pierre Quenneville; et al. (Engineering Structures, 2025)

ZnCo2O4/LaAlO3 transparent pn junction towards enhanced photoelectric response and stability via interfacial homogeneous high entropy oxide perovskite La(Cu0.2Co0.2Ni0.2Fe0.2Mn0.2)O3 QDs - Bo He; Yujia Huang; Rui Wang; Dingwei Wang; Chengyu Jia; Jun Cao; Lei Shi; Jiaqi Pan; Zhiguo Zhao; Chaorong Li (Chemical Engineering Journal, 2025)

Effects of earthworms on the performance of Lolium multiflorum, soil properties and microbial communities in its root-zone soil under cadmium stress - Xiao-Gai Wang; Bing-Nan Zhao; Zi-Yang Xie; Zhi-Huan Chen; Zhi-Hang Liu; Xiao Chen; Bo-Yang Lu; Jia-Ning Liu; Rui Zhang; Chao Si (Plant and Soil, 2025)

The potential of golden apple snail (Pomacea canaliculata) meat meal as an alternative protein source for juvenile Chinese mitten crab (Eriocheir sinensis) - Wenxiang Yao; Chunyan Zhang; Rui Jia; Sitong Zhao; Weibo Jiang; Guoan Hua; Sizhe Zhao; Apeng Lin; Jianguo Wang; Quan Wang (Frontiers in Marine Science, 2025)
This study investigated the effects of replacing dietary fish meal (FM) with golden apple snail ( Pomacea canaliculata ) meat meal (PCM) on growth performance, non-specific immunity and intestinal health of juvenile Chinese mitten crab ( Eriocheir sinensis ). Four hundred juvenile Chinese mitten crabs (2.39 ± 0.03) g were randomly distributed into five groups in quadruplicate (20 crabs per tank), and each group was fed with diets that replaced FM with PCM at 0% (FM-20, containing 200 g/kg FM), 25% (FM-15), 50% (FM-10), 75% (FM-5), and 100% (FM-0) for 8 weeks, respectively. The results showed that the growth, whole body composition, digestive enzyme activities, antioxidant performance, non-specific immunity, intestinal histology and microbiota composition of FM-15 and FM-10 groups all reached the same level as the FM-20 group ( P > 0.05). While the replacement ratio reached 75%, the FCR was significantly increased and the peritrophic membrane thickness was significantly decreased ( P< 0.05). When 100% FM was replaced, significantly decreased the growth performance, serum antioxidant and immune enzyme activities, mid-intestine folds height, width and the peritrophic membrane thickness ( P< 0.05), and significantly increased the abundance of intestinal harmful bacteria Vibrio ( P< 0.05). In conclusion, PCM can effectively replace 50% dietary FM (100 g/kg) without negative effects on the growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile E. sinensis .

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Soil degradation: A global threat to sustainable use of black soils - Rui LI; Wenyou HU; Zhongjun JIA; Hanqiang LIU; Chao ZHANG; Biao HUANG; Shunhua YANG; Yuguo ZHAO; Yongcun ZHAO; Manoj K. SHUKLA; Miguel Angel TABOADA (Pedosphere, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Gradient ethanol extracts of Coreopsis tinctoria buds: Chemical and in vitro fermentation characteristics - Shang Gao; Tiantian Li; Zhao-Rong Li; Bingwu Liao; Mouming Zhao; Chunxia Zhou; Donghui Luo; Rui-Bo Jia (Food Chemistry, 2025)

A new anti-inflammatory thujane monoterpenoid glycoside ester from Pittosporum heterophyllum Franch - Jia-Qi Ding; Sheng-Nan Guan; Yu-Feng Zhang; Zhao-Xuan Wang; Wei-Zhen Kong; Jun-Rui Ren; Xiu-Yun Zhang (Natural Product Research, 2025)

Programmable allosteric DNA nanomachine for ratiometric imaging of VEGF in tumor cells - Jia-Wei Liang; Yan-Mei Lei; Zhao-Peng Chen; Xue-Mei Zhou; Ya-Qin Chai; Ruo Yuan; Rui Du; Ying Zhuo (Chemical Engineering Journal, 2025)

Assessment of myelination development in neonatal rats using chemical exchange saturation transfer (CEST) 7-T MRI - Rui Wang; Shuxian Xu; Fenglin Jia; Yi Liao; Jiayi Li; Jing Liu; Fengyan Zhao; Haibo Qu (Experimental Brain Research, 2025)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Identification and validation of two quantitative trait loci showing pleiotropic effect on multiple grain-related traits in bread wheat (Triticum aestivum L.) - Wenjing Hu; Junchao You; Rui Yong; Die Zhao; Dongshen Li; Zunjie Wang; Jizeng Jia (Theoretical and Applied Genetics, 2024)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Synergistic effects of phosphorylation modification and protocatechuic acid copolymerization improve the physical and oxidation stability of high internal phase emulsion stabilized by perilla protein isolate - Qiaoli Zhao; Jinwei Li; Haili Qin; Rui Li; Kit Leong Cheong; Jianping Chen; Xiaofei Liu; Xuejing Jia; Bingbing Song; Zhuo Wang; Saiyi Zhong (Food Chemistry, 2024)

Phase change thermal interface film with bicontinuous and textured filler network for efficient wearable heat dissipation - Jia-Qing Zhao; Xiang Wang; Xun-Rui Wang; Hong-Wei Zhao; Mei-Na Lu; Wayne-Qiang Xu; Hong-En Nian; Jin-Hong Li (Chemical Engineering Journal, 2024)

Dual-emission rare-earth fluorescent nanomaterials for ratiometric and visual detection of N-acetylneuraminic acid and applications in information encryption and anti-counterfeiting - Jiaxin Wei; Qingyang Gu; Xinyu Er; Jia Sun; Lixia Zhao; Rui Qin; Haibo Jin (Analytica Chimica Acta, 2024)

Emulsion-filled surimi gel: A promising approach for enhancing gel properties, water holding capacity, and flavor - Qiaoli Zhao; Bin Zheng; Jinwei Li; Kit Leong Cheong; Rui Li; Jianping Chen; Xiaofei Liu; Xuejing Jia; Bingbing Song; Zhuo Wang; Saiyi Zhong (Trends in Food Science & Technology, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Portulaca oleracea L. polysaccharide ameliorates ulcerative colitis by regulating the immune system and gut microbiota - Yang Yang; Xiechen Zhou; Guiyan Jia; Hui Zhao; Yan Li; Junyang Cao; Zijian Guan; Rui Zhao (Food Bioscience, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Earthworms and Arbuscular Mycorrhizal Fungi Alleviated Salt Stress in Maize Seedlings by Regulating the Root Endodermis Diffusion Barrier - Binglei wang; Chong Wang; Lei Zhao; Xuelian Liu; Rui Xue; Jia Cao; Siping Li; Mengyao Guo; Huiying Huang (Journal of Plant Growth Regulation, 2024)

Mechanical and hydraulic characteristics of unvegetated or vegetated loess soils amended with xanthan gum - Jing Ni; Rui-Jie Zhao; Jia-Qi Chen; Xue-Yu Geng (Transportation Geotechnics, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Regulating the electronic state of SnO2@NiFe-LDH heterojunction: Activating lattice oxygen for efficient oxygen evolution reaction - Chaojie Yin; Fanghe Zhou; Chunliang Ding; Shengde Jin; Rui Zhu; Jiang Wu; Wenhao Li; Wu Yang; Jia Lin; Xinxia Ma; Jinao Deng; Zhongjun Zhao (Fuel, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

BODIPY Based OFF-ON Fluorescent Probe for Endogenous Carbon Monoxide Imaging in Living Cells - Lei Zhao; Rui Chen; Cheng Jia; Jiandong Liu; Guohua Liu; Tanyu Cheng (Journal of Fluorescence, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Occurrence, distribution and ecological risk assessment of herbicide residues in cropland soils from the Mollisols region of Northeast China - Rui Li; Wenyou Hu; Hanqiang Liu; Biao Huang; Zhongjun Jia; Feng Liu; Yuguo Zhao; Khalid Saifullah Khan (Journal of Hazardous Materials, 2024)

Reproducibility in nontarget screening (NTS) of environmental emerging contaminants: Assessing different HLB SPE cartridges and instruments - Wenhao Jia; He Liu; Yini Ma; Guolong Huang; Yaxiong Liu; Bo Zhao; Danping Xie; Kaibo Huang; Rui Wang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Novel insights into mass transfer-controlled radical-mediated co-pyrolysis of lignin with typical plastics - Yuyang Fan; Chao Liu; Zhengxue Zhang; Jia Ouyang; Fuli Deng; Ruixue Zhao; Huiyan Zhang; Rui Xiao (Chemical Engineering Journal, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

High titer (>100 g/L) ethanol production from pretreated corn stover hydrolysate by modified yeast strains - Rui Zhao; Hongshen Li; Qi Li; Zefang Jia; Shizhong Li; Ling Zhao; Shan Li; Yuwei Wang; Wenxin Fan; Ruoqi Ren; Zitong Yuan; Mengchan Yang; et al. (Bioresource Technology, 2024)

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

Three-dimensional visualization of the lymphatic, vascular and neural network in rat lung by confocal microscopy - Shitong Zhao; Jingjing Cui; Yuqing Wang; Dongsheng Xu; Yuxin Su; Jie Ma; Xuefeng Gong; Wanzhu Bai; Jia Wang; Rui Cao (Journal of Molecular Histology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Assessing resilience of sustainability to climate change in China's cities - Rui Zhao; Xia Li; Ying Wang; Zhenci Xu; Meiyu Xiong; Qian Jia; Fengting Li (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Featured immune characteristics of COVID-19 and systemic lupus erythematosus revealed by multidimensional integrated analyses - Xingwang Zhao; Mengjie Zhang; Yuying Jia; Wenying Liu; Shifei Li; Cuie Gao; Lian Zhang; Bing Ni; Zhihua Ruan; Rui Dong (Inflammation Research, 2023)

Agricultural intensification weakens soil multifunctionality by reducing fungal diversity - Rui Xue; Chong Wang; Lei Zhao; Jia Cao; Mengli Liu; Dong Zhang (Applied Soil Ecology, 2023)

Effects of dietary supplementation of Anabaena sp. PCC7120 expressing VP28 protein on survival and histopathology after WSSV infection in Macrobrachium nipponense - Yupei Tong; Jia Yang; Li Wang; Xiaoping Chi; Chan Zhu; Rong Yin; Le Zhang; Yaru Li; Chunyan Zhao; Rui Jia (Fish & Shellfish Immunology, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Characterizations of food-derived ellagic acid-Undaria pinnatifida polysaccharides solid dispersion and its benefits on solubility, dispersity and biotransformation of ellagic acid - Zhao-Rong Li; Rui-Bo Jia; Xueyuan Cai; Donghui Luo; Chong Chen; Mouming Zhao (Food Chemistry, 2023)

Experimental study on low-damage performance of Sliding Hinge Joint - Junrong Liu; Rui Zhang; Zhenduo Yan; Jiang-Yue Xie; Kim Eng Chouery; Liang-Jiu Jia; Ping Xiang; Xianzhong Zhao; Shahab Ramhormozian; Rajesh P. Dhakal; G. Charles Clifton; Gregory A. MacRae (Soil Dynamics and Earthquake Engineering, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Never in mitosis gene A-related kinase-6 deficiency deteriorates diabetic cardiomyopathy via regulating heat shock protein 72 - Shuangyin Shao; Lili Xiao; Meng Jia; Chuyang Zhang; Guojun Zhao; Rui Yao; Xiaofang Wang; Lu Gao (Journal of Molecular Medicine, 2023)

Understanding the Origin and Evolution of Tea (Camellia sinensis [L.]): Genomic Advances in Tea - Zai-Bao Zhang; Tao Xiong; Jia-Hui Chen; Fan Ye; Jia-Jia Cao; Yu-Rui Chen; Zi-Wei Zhao; Tian Luo (Journal of Molecular Evolution, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Iron-based nanomaterials reduce cadmium toxicity in rice (Oryza sativa L.) by modulating phytohormones, phytochelatin, cadmium transport genes and iron plaque formation - Pingfan Zhou; Peng Zhang; Mengke He; Yu Cao; Muhammad Adeel; Noman Shakoor; Yaqi Jiang; Weichen Zhao; Yuanbo Li; Mingshu Li; Imran Azeem; Like Jia; et al. (Environmental Pollution, 2023)

Sodium hydrosulfide alleviates aluminum toxicity in Brassica napus through maintaining H2S, ROS homeostasis and enhancing aluminum exclusion - Yan Yu; Jia Dong; Rui Li; Xue Zhao; Zonghe Zhu; Fugui Zhang; Kejin Zhou; Xianyong Lin (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Ameliorating C and N balance without loss of productivity by applying mulching measures in rainfed areas - Zihan Liu; Bingfan Wang; Zhaoyang Li; Chenxu Zhao; Rui Qian; Fangyuan Huang; Peng Zhang; Hui Li; ZhiKuan Jia (Agriculture, Ecosystems & Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Magnolol upregulates CHRM1 to attenuate Amyloid-β-triggered neuronal injury through regulating the cAMP/PKA/CREB pathway - Gemin Zhu; Yuan Fang; Xiaoli Cui; Ruihua Jia; Xiaogang Kang; Rui Zhao (Journal of Natural Medicines, 2022)

Characterization on the P-associated and agronomic traits as well as associated molecular processes in wheat under Pi deprivation condition - Ying-Jia Zhao; Xin-Yang Bai; Rui-Ze Lin; Fang-fang Li; Kai Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Weakened growth, cell division, and energy metabolism, but enhanced resistance, signaling, and anabolism: responses of Ulva prolifera to copper elucidated by omics - Chuner Cai; Xuanhong Liu; Hui Zhao; Ting Jiang; Rui Jia; Peimin He (Journal of Applied Phycology, 2021)

A high-resolution timescale for the Miocene Shanwang diatomaceous shale lagerstätte (China): development of Wavelet Scale Series Analysis for cyclostratigraphy - Jifeng Yu; Xinlong Pang; Wenzhao Fu; Jason Hilton; Mingmei Liang; Zongkai Jiang; Xiuli Zhao; Wenyan Qiao; Suo Shi; Diandong Zhang; Huitao Cao; Haibo Jia; et al. (Geosciences Journal, 2021)

Numerical modeling of 3D DC resistivity method in the mixed space-wavenumber domain - Shi-Kun Dai; Jia-Xuan Ling; Qing-Rui Chen; Kun Li; Qian-Jiang Zhang; Dong-Dong Zhao; Ying Zhang (Applied Geophysics, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Herbidospora solisilvae sp. nov., a novel cellulose-degrading actinobacterium isolated from forest soil - Mingying Yu; Rui Zhou; Jingjing Li; Liyuan Han; Han Wang; Siyu Zhang; Junwei Zhao; Xiangjing Wang; Jia Song; Wensheng Xiang (Antonie van Leeuwenhoek, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Safety Analysis Control Measures of Multiple Mining Soft Rock Roadways - Rui Peng; Meiling Fang; Ruile Ren; Qifeng Zhao; Hanwen Jia (Geotechnical and Geological Engineering, 2021)

Dynamic Response of Phragmites australis and Suaeda salsa to Climate Change in the Liaohe Delta Wetland - Yushu Zhang; Wenying Yu; Ruipeng Ji; Yijun Zhao; Rui Feng; Qingyu Jia; Jinwen Wu (Journal of Meteorological Research, 2021)

Indole alkaloid glycosides from Isatis tinctoria roots - Dongdong Zhang; Kang Du; Yitian Zhao; Songshan Shi; Yingchun Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2021)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Hand, foot, and mouth disease in Changsha City, China, 2009–2017: a new method to analyse the epidemiological characteristics of the disease - Dong Yang; Ruchun Liu; Lan Ye; Qingqing Hu; Jia Rui; Yinzhu Zhou; Heng Zhang; Xixing Zhang; Benhua Zhao; Tianmu Chen (Infectious Diseases, 2020)

Filler improvement and purification effects of constructed rapid infiltration facility - Rui-song Zhao; Jia-ke Li; Chao Guo; Fan Li; Huai-en Li (Environmental Science and Pollution Research, 2019)

Depositional facies and stratal cyclicity of carbonate successions in the Yingshan and Yijianfang Group (Lower-Middle Ordovician) in Yuejin-Tuoputai Region, Tarim Basin, NW China - Cunli Jiao; Zhao Xue-Qin; Rui Zhao; Li Hui-Li; Liu Tian-Jia; Zhao Jia-Hui (Carbonates and Evaporites, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Fast 3D forward modeling of the magnetic field and gradient tensor on an undulated surface - Kun Li; Long-Wei Chen; Qing-Rui Chen; Shi-Kun Dai; Qian-Jiang Zhang; Dong-Dong Zhao; Jia-Xuan Ling (Applied Geophysics, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Stocking density effects on growth and stress response of juvenile turbot (Scophthalmus maximus) reared in land-based recirculating aquaculture system - Baoliang Liu; Rui Jia; Kuifeng Zhao; Guowen Wang; Jilin Lei; Bin Huang (Acta Oceanologica Sinica, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Binariimonas pacifica gen. nov., sp. nov., a Novel Marine Bacterium of Family Sphingomonadaceae Isolated from East Pacific Ocean Surface Seawater - Zhao Zhao; Jia Sun; Rui Zhang; Nianzhi Jiao (Current Microbiology, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Association between interferon gamma +874 T>A polymorphism and acute renal allograft rejection: evidence from published studies - Yu-Zheng Ge; Ran Wu; Rui-Peng Jia; Hao Liu; Peng Yu; Yan Zhao; Yu-Ming Feng (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Pollen morphology and ontogeny of Maianthemum bifolium (L.) F.W. Schmidt in China - Bing-Xiao Chen; Chun-Hai Zhao; Yun-Yun Zhao; Xiao-Rui Liu; Jia-Xi Liu (Plant Systematics and Evolution, 2013)

Exogenous hydrogen sulfide attenuates diabetic myocardial injury through cardiac mitochondrial protection - Xin Zhong; Leihong Wang; Yuwen Wang; Shiyun Dong; Xiaoning Leng; Jing Jia; Yajun Zhao; Hulun Li; Xinying Zhang; Changqing Xu; Guangdong Yang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2012)

Pollen development of Cardiocrinum giganteum (Wall.) Makina in China - Hong-Na Chen; Chun-Hai Zhao; Xiao-Rui Liu; Jia-Xi Liu (Plant Systematics and Evolution, 2012)

OVCA1 inhibits the proliferation of epithelial ovarian cancer cells by decreasing cyclin D1 and increasing p16 - Fandou Kong; Rui Tong; Lingyu Jia; Wei Wei; Xiaoyan Miao; Xinyu Zhao; Wenping Sun; Guang Yang; Chunyan Zhao (Molecular and Cellular Biochemistry, 2011)

Pollen morphology of Hosta Tratt. in China and its taxonomic significance - Jia-Xi Liu; Chun-Hai Zhao; Xiao-Rui Liu; Yi-Zhen Xi; Yu-Long Zhang (Plant Systematics and Evolution, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Activity of the Antimicrobial Peptide and Thanatin Analog S-thanatin on Clinical Isolates of Klebsiella pneumoniae Resistant to Conventional Antibiotics with Different Structures - Guo-Qiu Wu; Jia-Xuan Ding; Lin-Xian Li; Hai-liang Wang; Rui Zhao; Zi-Long Shen (Current Microbiology, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

AtMTM1, a novel mitochondrial protein, may be involved in activation of the manganese-containing superoxide dismutase in Arabidopsis - Zhao Su; Mao-Feng Chai; Ping-Li Lu; Rui An; Jia Chen; Xue-Chen Wang (Planta, 2007)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

The wheat TaGI1, involved in photoperiodic flowering, encodesan Arabidopsis GI ortholog - Xiang Yu Zhao; Mao Sen Liu; Jia Rui Li; Chun Mei Guan; Xian Sheng Zhang (Plant Molecular Biology, 2005)